A comparative evaluation of manual and powered brushing on oral health and microbial status of mentally challenged individuals - Kharidi Laxman Vandana; Pramod Vinayak Tatuskar; Narayan Narendra Valavalkar (Wolters Kluwer Medknow Publications, 2020)
Background: Tooth brushing is a very simple and effective method for removing daily dental deposits and for preventing dental and periodontal diseases. In physically or mentally challenged person, there arises difficulty in oral hygiene maintenance so that oral hygiene methods may need to be simplified or modified to suit the individual situation. Methodology: Thirty individuals of age group 15-30 years with mild to moderate degree of mental retardation were selected. A randomized double-blind split-mouth design with Clinical Phase-i (aided brushing) and Clinical Phase-ii (unaided brushing) with a washout period of 3 days was conducted. The study duration was for 0-45 days. Two types of brushing that is manual and powered brushing were done. The recording of all clinical and microbial parameters were done on 0th day and 21st day while the clinical parameters were recorded up to 45th day. Results: On intragroup comparison, throughout the study phases, both manual and powered brushing significantly reduced the Quigley-Hein plaque index (48%), gingival bleeding index (GBI) (44%), and modified gingival index (52%). The Pearson correlation between GBI and periodontal pathogens like Prevotella internedia, Porphyromonas gingivalis, and Fusobacterium nucleatum showed statistically significant relation (P < 0.05) in powered brushing group. Conclusion: Powered toothbrush was more effective than manual toothbrush in reducing plaque levels and microbial count in the mentally challenged individuals. The Colgate 360 tooth brush is advisable to mentally challenged individuals.